System Integration Model Based on Open Source Software (Oss) - Kamsuriah, Ahmad; Azwan, Mohamed; Reduan, Samad (2009)
Application system is an important component to support business organizations. Information, communication and information technology have made developing business becomes very competitive. It is very crucial for companies to have fast and accurate access to mission-critical business information in order to maintain its competitiveness. The ability to establish network connections between the existing systems becomes a must in order to optimize the use of critical information. To realize this, the implementation of system integration looks promising. However, system integration process is not an easy task because it involves variety of systems with different organizations backgrounds. The main objective of this paper is to propose an integration model that is generic and easily adapted by many organizations. The Information Management Division, Public Sector Department in Malaysia is chosen as a case study. The systems used in this department will be analyzed and problems faced will be identified. Research methodology conducted includes the Analysis Phase, Design Phase, Development Phase and Testing Phase. In order to support the proposed model, prototype called myIntegration is implemented based on OpenSyncro. OpenSyncro is an open source software (OSS) meant for Enterprise Application Integration (EAI). The Testing Phase was carried out by taking into account the actual test scenario involving the Department A (owner of the Malaysian Personal Record) and Department B (Human Resources Manager of Malaysian Civil Servants). Tests conducted have shown that the exchange of information between the Department A and B have been successfully realized. The finding from this research, where a new integration model has been created, can be referred by any government or private organizations in developing their systems integration facilities. The model also besides reducing the requirement of hardware; also reduces the dependency to proprietary products. In addition, the prototype developed, which based on OpenSyncro is capable in providing an alternative solution to the IT community to anchor any systems integration project at a lower cost and in a user friendly environment.